2016
DOI: 10.1017/s1368980016002688
|View full text |Cite
|
Sign up to set email alerts
|

Differences in expenditure and amounts of fresh foods, fruits and vegetables, and fish purchased in urban and rural Scotland

Abstract: Objective: To quantitatively analyse expenditure on all fresh foods, fruits and vegetables (F&V) and fish across urban and rural households in Scotland. Fresh foods were chosen since, in general, they are perceived to contribute more to health than processed foods. Design: Descriptive analysis of purchase data of all foods brought into the home during 2012 from the Kantar Worldpanel database. Purchase data were restricted to fresh, unprocessed and raw foods or 'fresh to frozen' foods where freezing was part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Chaudhary et al [2] describe food availability as being related to "ease of physical access to food" and food affordability. de Roos et al [52] found that: "Contrary to previous studies, purchase data show that access to and average prices of fresh foods generally, and F&V and fish specifically, are broadly similar between urban and rural areas". Therefore, with regards to the UK context, affordability of beef products is the issue, rather than availability.…”
Section: Availabilitymentioning
confidence: 73%
“…Chaudhary et al [2] describe food availability as being related to "ease of physical access to food" and food affordability. de Roos et al [52] found that: "Contrary to previous studies, purchase data show that access to and average prices of fresh foods generally, and F&V and fish specifically, are broadly similar between urban and rural areas". Therefore, with regards to the UK context, affordability of beef products is the issue, rather than availability.…”
Section: Availabilitymentioning
confidence: 73%
“…Two studies conducted with Kantar data in Scotland found that households with a higher level of deprivation were less likely to achieve the revised Scottish Dietary Goals [56][57]. Another paper that used Kantar data in Scotland analysed the expenditure on fresh foods and fruits and vegetables across urban and rural households [58]. They found that rural households spent the most on fresh foods, fruits and vegetables but prices in urban locations were significantly higher, suggesting that factors other than availability and price were causing the difference [58].…”
Section: Resultsmentioning
confidence: 99%
“…Since realizing that food and the broader built environment are related to the risk of incurring chronic diseases [ 1 , 2 ], investigators have conducted many studies on food access. A majority of this research [ 3 , 4 , 5 , 6 , 7 ] has examined the access to fresh vegetables and fruits. There is limited literature on access to energy-dense and nutrient-poor (EDNP) foods, such as sugary beverages and sweet snacks.…”
Section: Introductionmentioning
confidence: 99%
“…We can better understand access to food by studying how neighborhood food access affects purchases of EDNP foods. The food purchasing literature provides, at most, moderate evidence that neighborhood food availability relates to the amount of fresh foods purchased or the food purchased as a total based on an aggregated purchasing index [ 6 , 11 , 12 , 13 ]. Because of the ubiquity of EDNP foods and their relatively low cost [ 14 , 15 ], it is not known whether people rely on the immediate neighborhood to purchase EDNP foods.…”
Section: Introductionmentioning
confidence: 99%